Routine Blood Parameters in Elite Soccer Players - Meyer, T.; Meister, S. (International Journal of Sports Medicine, 2011)
Often blood screening is repeatedly done in elite athletes although training and competition can affect its results and normal ranges for highly active individuals are widely unknown. This study was conducted to provide reference data in professional soccer players. 467 male soccer players of the 2 highest German leagues were observed over an entire season. Venous blood sampling was conducted 4 times in a standardized manner to determine complete blood count, AST, ALT, CK, creatinine, urea, uric acid, cholesterol, electrolytes, ferritin, CRP and TSH.There were significant changes during the season in hematocrit, creatinine, uric acid (decrease), CK, AST, urea, sodium, potassium, magnesium, and TSH (increase). Only the changes in hematocrit and CK were large enough to possibly interfere with clinical decisions in soccer players. Upper limits of the 95% confidence intervals exceeded population reference ranges slightly in AST, urea, creatinine, and potassium. The mean intraindividual coefficient of variation was below 10% in complete blood count (except leukocytes), creatinine, uric acid, total cholesterol, and all electrolytes. There seems to be a profound effect of elite soccer training and competition on hematocrit (plasma volume) and CK only. Spontaneous variability of most parameters is too small to justify repeated sampling only for routine screening. Trial Registration: NCT00946855 Effect of Elite Soccer Training on Routine Laboratory Parameters (SOCCERLAB), http://www.clinicaltrials.gov/ct2/show/NCT00946855?term=soccerlab&rank=1
Keywords: athletes; exercise; reference range; plasma volume; variability